Textbook of biochemistry with clinical correlations; Textbook of biochemistry with clinical correlations - Devlin, Thomas M. Ed.; Devlin, Thomas M. Ed. (New Jersey, John Wiley, 2011)
This book presents a clear and precise discussion of the biochemistry of eukaryotic cells, particularly those of mammalian tissues, relates biochemical events at a cellular level to the subsequent physiological processes in the whole animal, and cites examples of abnormal biochemical processes in human disease. The organization and content are tied together to provide students with the complete picture of biochemistry and how it relates to human diseases.
Keywords: Biochemistry; Chemistry; Botany